Anterior nucleus of the thalamus seizure detection in ambulatory humans. (21st August 2021) - Gregg, Nicholas M.; Marks, Victoria S.; Sladky, Vladimir; Lundstrom, Brian N.; Klassen, Bryan; Messina, Steven A.; Brinkmann, Benjamin H.; Miller, Kai J.; Van Gompel, Jamie J.; Kremen, Vaclav; Worrell, Gregory A.
Abstract: There is a paucity of data to guide anterior nucleus of the thalamus (ANT) deep brain stimulation (DBS) with brain sensing. The clinical Medtronic Percept DBS device provides constrained brain sensing power within a frequency band (power‐in‐band [PIB]), recorded in 10‐min averaged increments. Here, four patients with temporal lobe epilepsy were implanted with an investigational device providing full bandwidth chronic intracranial electroencephalogram (cEEG) from bilateral ANT and hippocampus (Hc). ANT PIB‐based seizure detection was assessed. Detection parameters were cEEG PIB center frequency, bandwidth, and epoch duration. Performance was evaluated against epileptologist‐confirmed Hc seizures, and assessed by area under the precision‐recall curve (PR‐AUC). Data included 99 days of cEEG, and 20, 278, 3, and 18 Hc seizures for Subjects 1–4. The best detector had 7‐Hz center frequency, 5‐Hz band width, and 10‐s epoch duration (group PR‐AUC = .90), with 75% sensitivity and .38 false alarms per day for Subject 1, and 100% and .0 for Subjects 3 and 4. Hc seizures in Subject 2 did not propagate to ANT. The relative change of ANT PIB was maximal ipsilateral to seizure onset for all detected seizures. Chronic ANT and Hc recordings provide direct guidance for ANT DBS with brain sensing.